The influence of organizational structure, resources and culture on project performance: A study among construction firms in Penang - Shah Nizam, Osman (2017)
The purpose of this study is to investigate on the influence of organizational structures, resources and cultures on project performance among construction firms in Penang. A survey of a representative sample of 142 respondents was used in this study. This study is a quantitative method and the data from questionnaires were analyzed using Statistical Package for Social Science (SPSS) 22.0. Multiple regression analyses were performed to tests the hypotheses of the study. The findings confirmed that there were two hypotheses, organizational structures and cultures have a positive significant association with project performance. The primary contribution in this study is to enhance the understanding on the significant factors that influence on project performance among managers/contractors in construction firms in Penang.